Pitt Hopkins-Like Syndrome 1 with Novel CNTNAP2 Mutation in Siblings. (November 2021) - Mittal, Rea; Kumar, Ashutosh; Ladda, Roger; Mainali, Gayatra; Aliu, Ermal
Pitt Hopkins-like syndrome 1 (PTHLS1, OMIM # 610042) is an ultra-rare autosomal recessive condition with a prevalence of <1/1, 000, 000. Intragenic deletions of CNTNAP2 has been implicated in PTHLS1, however to our knowledge a compound heterozygous deletion of exon 4 and a c.1977_1989del13; p.V660Ffsx9 frameshift variant have not been published previously. In this case report, the proband is a seven year old female with PTHLS1, developmental delay, autism spectrum disorder, focal epilepsy, hypotonia, refractory errors, strabismus, and obstructive sleep apnea. Whole exome sequencing analysis revealed biallelic pathogenic variants of the CNTNAP2 gene. Proband has a three year old sister who has who has a similar phenotype including, developmental delay, epilepsy, gait abnormality, refractory errors, strabismus. Family variants were tested and she shared the same CNTNAP2 variants as her sister. The sisters described highlight two novel variants leading to PTHLS1. Genetic workup is essential in identification and management guidance in these populations.